Propaganda and Myth: Discourse Battle on Social Media in the Indonesian Presidential Election - Aminulloh, Akhirul; Artaria, Myrtati Dyah; Setiamandani, Emei Dwinanarhati (Unitri Press, 2024)
Propaganda on social media in the 2019 Indonesian presidential election became the arena for the discourse and narrative battle between the issues of communism and the caliphate that centered on presidential candidates Joko Widodo and Prabowo Subianto. Myth-based propaganda techniques manipulate discourse in order to influence public opinion. This study used Fairclough's critical discourse analysis method with a research object focusing on the issue of communism and the caliphate in social media. The data was collected using a variety of documentation techniques, including intertextuality, literature study, and tweets posted on the Twitter platform between January and March of 2019. The data analysis technique used three dimensions of Fairclough's critical discourse analysis: description, interpretation, and explanation. The results of this study indicate that the discourse battle of Joko Widodo as a communist henchman and Prabowo Subianto as pro-caliphate is propaganda to manipulate public opinion on social media to win the 2019 presidential election. The discourse about the PKI revival if Joko Widodo wins is moved by status quo groups and radical Islamic groups such as FPI and HTI, while the discourse on establishing a caliphate system in Indonesia if Prabowo Subianto wins is moved by nationalist jargon groups. Discourses about the PKI revival and the caliphate system’s establishment are myths in the form of narratives periodically produced and reproduced for political reasons. Despite evidence to the contrary, supporters continue to believe in this myth. Abstrak Propaganda di media sosial dalam pemilihan presiden Indonesia tahun 2019 menjadi arena pertarungan wacana dan narasi antara isu komunisme dan khilafah yang berpusat pada pasangan calon presiden Joko Widodo dan Prabowo Subianto. Penelitian ini menggunakan metode analisis wacana kritis Fairclough dengan objek penelitian yang berfokus pada isu komunisme dan khilafah di media sosial. Data dikumpulkan menggunakan berbagai teknik dokumentasi, termasuk intertekstualitas, studi pustaka, dan cuitan yang diunggah di platform Twitter antara Januari dan Maret 2019. Teknik analisis data menggunakan tiga dimensi analisis wacana kritis Fairclough. Hasil penelitian ini menunjukkan bahwa pertarungan wacana Joko Widodo sebagai antek komunis dan Prabowo Subianto sebagai pro-khilafah adalah propaganda untuk memanipulasi opini publik di media sosial untuk memenangkan pemilihan presiden 2019. Wacana kebangkitan PKI jika Joko Widodo menang digerakkan oleh kelompok status quo dan kelompok Islam radikal seperti FPI dan HTI, sedangkan wacana pembentukan sistem khilafah di Indonesia jika Prabowo Subianto menang digerakkan oleh kelompok jargon nasionalis. Wacana kebangkitan PKI dan pembentukan sistem khilafah merupakan mitos dalam bentuk narasi yang diproduksi dan direproduksi secara berkala untuk kepentingan politik.